2016
DOI: 10.1155/2016/7945619
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perioperative Ranibizumab Injections for Diabetic Macular Edema in Patients Undergoing Cataract Surgery

Abstract: Purpose. To compare the efficacy of perioperative ranibizumab injections on diabetic macular edema (DME) in patients undergoing cataract surgery. Methods. This study included 59 eyes of 59 patients. All patients had advanced cataract with DME and underwent an uneventful phacoemulsification surgery. There were 3 subgroups. The first group received intravitreal ranibizumab injection 2 weeks preoperatively, the second group received intraoperatively, and the third group received 2 weeks postoperatively. Follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…The postoperative CMT in the observation group decreased significantly, while that in the control group increased slightly. These results were close to those of Yumusak et al [ 11 ]. Denniston et al found that the concentration of VEGF in the aqueous humor of diabetic patients increased from 68 pg/ml at baseline to 723 pg/ml one day after surgery, yielding a tenfold increase [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…The postoperative CMT in the observation group decreased significantly, while that in the control group increased slightly. These results were close to those of Yumusak et al [ 11 ]. Denniston et al found that the concentration of VEGF in the aqueous humor of diabetic patients increased from 68 pg/ml at baseline to 723 pg/ml one day after surgery, yielding a tenfold increase [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that intraoperative intravitreal ranibizumab with cataract surgery is more effective than preoperative or postoperative injection for DME although an ongoing treatment is needed in these patients. [ 50 ] Steroids, on the other hand, have shown to be effective for persistent or refractory DME. [ 50 ] Dexamethasone has potentially less risk of intraocular pressure (IOP) elevation and cataract formation compared to fluocinolone acetonide and triamcinolone acetate.…”
Section: Discussionmentioning
confidence: 99%
“…[ 50 ] Steroids, on the other hand, have shown to be effective for persistent or refractory DME. [ 50 ] Dexamethasone has potentially less risk of intraocular pressure (IOP) elevation and cataract formation compared to fluocinolone acetonide and triamcinolone acetate. [ 51 ] Furthermore, the intravitreal dexamethasone implants and fluocinolone implants require less frequent injections.…”
Section: Discussionmentioning
confidence: 99%
“…Because preexisting DME can increase the risk of ME progression by 20%–50%, intravitreal antiVEGF agents are recommended perioperatively[ 45 , 46 ]. Steroids, on the other hand, have been shown to be effective for persistent or refractory DME[ 47 ]. Dexamethasone implants and fluocinolone implants resulted in significant improvement in clinically significant ME and visual outcomes[ 48 , 49 ].…”
Section: Preoperative Evaluationmentioning
confidence: 99%